PS 11-27 CARDIOMETABOLIC RISK GUIDELINES IN PRIMARY CARE: A NOVEL APPROACH TO CLINICAL GUIDELINE PRESENTATION IN HYPERTENSION AND COMORBIDITIES. (September 2016) - Almustafa, Bader; Alfaraj, Nada; Aleid, Nawal; Almobarak, Aamal; Hejlis, Manal; Alsalman, Eman; Mogharbel, Kholoud
Abstract : Objective: Cardiometabolic risk (CMR), such as hypertension, diabetes mellitus, dyslipidemia, obesity and smoking used to coexist. More than half of patients are presenting with 3 or more conditions in the primary care (PHC). Thus, it mandates primary care provider (PCP) to follow multiple guidelines for one patient. The complexity and multiplicity of these guidelines are major barriers to implementation. This effort tries to address these barriers, and develop a translational guideline for CMR management. Design and Method: The process involved a broad group of PHC professionals, including physicians, nurses, pharmacists, educationists, dietitians and guideline developers. Key Evidence-based reviews, meta-analyses and guidelines from the last 5 years were used as reference. ADAPTE methods and AGREE instrument were used in the development and assessment of each aspect of the guidelines, respectively. Results: The scope of the guideline is to provide a comprehensive approach to the management of CMR factors; include nutrition therapy, physical activity recommendations, pharmacologic therapy, self-management, as well as prevention and diagnosis of CMR-associated complications; provide suggestions to the management of the delivery system, the clinical information and the quality of care. Sections of the guideline include Methodology; General Algorithms; Screening; Assessment; Control; Non-pharmacologic management; Tools and tips for the PHC provider; and Quality Management. Self-management, screening of depression, building a nurse-led clinic, effective use of clinical information and quality measures are among the tools provided. The guideline pays special attention to CVR reduction, foot care, renal assessment, and screen of all > 45 years of age and obese for CMR. Conclusions: Cardiometabolic risk Guideline is a novel tool to overcome complexity of taking care after hypertensive patients and its comorbidities. It offers a common reference for assessment, management and total quality care.